Composition and diversity of gut microbiota in diabetic retinopathy - Bai, Jianhao; Wan, Zhongqi; Zhang, Yuanyuan; Wang, Tianyu; Xue, Yawen; Peng, Qing (Frontiers in Microbiology, 2022)
Objective: Diabetic retinopathy (DR) is one of the most common complications in type 2 diabetes mellitus. The current study examined the composition, structure, and function of the gut microbiota in DR to establish a correlation between gut microbiota and clinical characteristics. Methods: A total of 50 stool samples were collected from 50 participants, including 25 DR patients and 25 healthy controls (HCs). 16S ribosomal RNA gene sequencing was used to analyze the gut microbial composition in the two groups. DNA was extracted from the fecal sample using the MiSeq platform. Results: Microbial structure and composition of DR patients were different from that of HCs. The microbial richness of gut microbiota in DR was higher than that of normal individuals. The microbiome alterations of DR patients were associated with disrupted Firmicutes, Bacteroidetes, Synergistota, and Desulfobacterota phyla. In addition, increased levels of Bacteroides, Megamonas, Ruminococcus_torques_group, Lachnoclostridium, and Alistipes and decreased levels of Blautia, Eubacterium_ hallii_group, Collinsella, Dorea, Romboutsia, Anaerostipes, and Fusicatenibacter genera were observed in the DR groups than in the healthy individuals. Additionally, a stochastic forest model was developed to identify a set of biomarkers of the seven bacterial genera that can differentiate patients with DR from those with HC. Due to these alterations, microbial communities exhibited varied functions in the two groups. Conclusion: The altered composition and function of gut microbiota in DR indicated a potential for the gut microbiome to serve as the noninvasive biomarker, improve the clinical diagnostic methods of DR, and identify the putative therapeutic targets.